2018
DOI: 10.1097/igc.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Patterns and Survival of Gynecological Sarcoma in Germany: Analysis of Population-Based Cancer Registry Data on 1066 Women

Abstract: Despite the rareness of GS, the size of the data set allows for a differentiation of subtypes according to morphology and site of origin. Clinically relevant differences in incidence and prognosis between subgroups were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
2
6
1
1
Order By: Relevance
“…A percentage range of 40-46 and 30-45% has been reported for leiomyosarcomas carcinosarcomas, respectively. In contrast to these findings, the range and percentage was estimated to 86-97% for ESSs and to 69% for adenosarcomas, respectively (20,(26)(27)(28). The rates reported in the present study were lower than those previously published.…”
Section: Uterine Sarcomas By Histological Type ----------------------contrasting
confidence: 99%
“…A percentage range of 40-46 and 30-45% has been reported for leiomyosarcomas carcinosarcomas, respectively. In contrast to these findings, the range and percentage was estimated to 86-97% for ESSs and to 69% for adenosarcomas, respectively (20,(26)(27)(28). The rates reported in the present study were lower than those previously published.…”
Section: Uterine Sarcomas By Histological Type ----------------------contrasting
confidence: 99%
“…Other studies have reported similar results, ranging from 70 to 90%. Furthermore, the most common morphological subtype among uterine sarcomas was leiomyosarcoma (37%), which was also in accordance with most of the previous studies 5–7,14–17 . However, a study reporting the results from SEER database and also a study in Japan found that carcinosarcoma was the most common type (53% and 47%) in spite of our result that was less than one‐fifth of them (9%) followed by leiomyosarcoma (24% and 36%) 18,19 .…”
Section: Discussionsupporting
confidence: 91%
“…In a population‐based study in Germany, the annual ASR of all GS cases was 6.6 in one million women (world standard population). In this study, uterine sarcomas had an incidence rate of 5.8 per million individuals 14 . Our study showed an incidence rate of 6.13 and 4.7 per million females for all sites combined and uterine sarcomas, respectively.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Together with the various primary sites, they make up a large number of combinations that vary tremendously in terms of survival and clinical treatment, which means that same histological subtype in different sites may need completely different therapies 6,31 . The rarity of STSs and the even smaller number of cases in each combination further add to the difficulty faced by researchers and physicians.…”
Section: Discussionmentioning
confidence: 99%